2011
DOI: 10.1182/blood-2010-12-322909
|View full text |Cite
|
Sign up to set email alerts
|

Escalating intravenous methotrexate improves event-free survival in children with standard-risk acute lymphoblastic leukemia: a report from the Children's Oncology Group

Abstract: Children's Cancer Group-1991 selected 2 components from the Children's Cancer Group studies shown to be effective in high-risk acute lymphoblastic leukemia and examined them in children with National Cancer Institute standard-risk acute B-precursor lymphoblastic leukemia. These were (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
123
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(127 citation statements)
references
References 34 publications
4
123
0
Order By: Relevance
“…Two of the most important glucocorticoids used for treating childhood ALL are PRED and DEX. Although DEX consistently shows higher antileukemic activity both in vitro and in vivo 4,[15][16][17] , PRED is used in most chemotherapy protocols due to its better toxicity profile. DEX administration is associated with higher risk of myopathy, adverse neuro-psychiatric events, osteonecrosis, sepsis, fungal infections, diabetes and pancreatitis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Two of the most important glucocorticoids used for treating childhood ALL are PRED and DEX. Although DEX consistently shows higher antileukemic activity both in vitro and in vivo 4,[15][16][17] , PRED is used in most chemotherapy protocols due to its better toxicity profile. DEX administration is associated with higher risk of myopathy, adverse neuro-psychiatric events, osteonecrosis, sepsis, fungal infections, diabetes and pancreatitis 7 .…”
Section: Discussionmentioning
confidence: 99%
“…Children with ALL who present with CNS disease (CNS3) at diagnosis are at a higher risk of treatment failure (both within the CNS and systemic involvement) than are the children who are classified as CNS1 or CNS2 [19]. Some studies have reported increased risk of CNS relapse and/or inferior EFS in CNS2 patients, compared with CNS1 children, [19,17] while others have not such involvement [18,15,20].…”
Section: Cns3 (Cns Disease)mentioning
confidence: 99%
“…Some studies have reported increased risk of CNS relapse and/or inferior EFS in CNS2 patients, compared with CNS1 children, [19,17] while others have not such involvement [18,15,20].…”
Section: Cns3 (Cns Disease)mentioning
confidence: 99%
See 2 more Smart Citations